Business model research proposal: novel business model concepts based on sustainable multiple customer value creation in a selected country - Kita, Peter; Šimberová, Iveta (Univerzita Pardubice, 2018)
The article’s objective is to propose a research framework that could describe an industry, structured by the industry’s specific performance indicators, through the lens of its business models as well as identify the specific features of novel business models. The approach is based on combining various approaches to business model research and propose a methodology which examines an selected industry, in this case a sector of the Czech chemical industry, through the lens of its business models and aims to provide novel business model concepts based on sustainable multiple customer value creation. The framework connects the theoretical concepts of business models, sustainable value added, and multiple customer value creation. The framework appropriates environmental and social aspects of the business model’s value proposition to the underlying strategy and gauges it by sustainable value added. The resulting business model concepts serve as an overview and incentive to further develop novel business model designs within the selected industry.
Keywords: multiple value; sustainable business model concept; sustainable value added; majority business model; minority business model; chemical industry; M21